THE USE OF PROBLEM-BASED LEARNING TO IMPROVE STUDENTS’ UNDERSTANDING OF ENGLISH MATERIALS AT SMAN 1 BARRU - Muh. Fadhil Rusdi; Chairil Anwar Korompot; Nur Aeni (JTechLP: Journal of Technology in Language Pedagogy, 2026)
The purpose of this study is to ascertain whether problem-based learning can improve students' understanding of English-language material. Pre-experimental and one-group pretest-posttest designs were employed in this quantitative study. Twelve classes from UPT SMAN 1 Barru's class XI F made up the study population. 35 pupils from class XI F 10 made up the study's sample. Random sampling was used to choose the study's sample. A 20-question multiple-choice test served as the research tool. The test was given twice: once before therapy (pretest) and once following treatment (posttest). Four meetings were conducted using the problem-based learning approach. The average pretest score was 50.00, while the average posttest score rose to 82.42, according to the data analysis results. Furthermore, a statistically significant increase with a 2-tailed sig. 0.000 < 0.05 was found in the paired sample t-test study. The data analysis led to the acceptance of the alternative hypothesis (H1) and the rejection of the null hypothesis (H0). This suggests that using problem-based learning techniques can be beneficial and the best option for raising students' understanding of English-language content. In order to improve students' understanding of the English language curriculum at SMAN 1 Barru, problem-based learning techniques can be incorporated as an interesting and dynamic teaching strategy.